2019
DOI: 10.1590/1413-81232018249.24692017
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de açúcares de adição por adolescentes em estudo de base populacional

Abstract: Resumo Objetivou-se estimar a prevalência de ingestão de açúcares de adição dentro do limite máximo de 5% da energia total da dieta, segundo variáveis demográficas, socioeconômicas, de comportamentos relacionados à saúde e estado nutricional, em adolescentes. Trata-se de estudo transversal de base populacional, com amostra por conglomerados e em dois estágios. A quantidade de açúcar livre da dieta foi estimada por meio do Recordatório de 24 horas. Dos 924 adolescentes avaliados, apenas 20,1% (IC95%: 16,8-23,9)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
4
0
3
Order By: Relevance
“…This result is probably due to the bitter taste of cocoa, although the formulations contained a higher amount of 50% cocoa rather than 100% cocoa The bitter taste in the formulation can be adjusted according to the consumption habits and age group, due to different sensory preferences of cocoa since the bitter taste pleases mainly consumers accustomed to consuming bitter cocoa. Thus, to increase the sensory scores, other ingredients that reduce the residual bitterness should be used in the formulations Although sucrose is one of the ingredients that can contribute to sweetness, studies have shown that Brazilians consume this ingredient more than the recommended daily amount (Braz et al., 2019; Levy et al., 2012), thus further studies are required to find other alternatives to reduce the bitterness of these products.…”
Section: Resultsmentioning
confidence: 99%
“…This result is probably due to the bitter taste of cocoa, although the formulations contained a higher amount of 50% cocoa rather than 100% cocoa The bitter taste in the formulation can be adjusted according to the consumption habits and age group, due to different sensory preferences of cocoa since the bitter taste pleases mainly consumers accustomed to consuming bitter cocoa. Thus, to increase the sensory scores, other ingredients that reduce the residual bitterness should be used in the formulations Although sucrose is one of the ingredients that can contribute to sweetness, studies have shown that Brazilians consume this ingredient more than the recommended daily amount (Braz et al., 2019; Levy et al., 2012), thus further studies are required to find other alternatives to reduce the bitterness of these products.…”
Section: Resultsmentioning
confidence: 99%
“…The literature demonstrates that sugar intake, for example, is considered a risk factor for several diseases, including dental caries and obesity 26 . This information should be discussed in order to empower parents/caregivers in terms of providing preventative care for their children 27 . Collective measures are also important, such as a sugar tax and the proper labeling of unhealthy foods, which imply a reduction in the availability of foods with a high potential to develop chronic diseases, such as obesity, diabetes, and dental caries 4 …”
Section: Discussionmentioning
confidence: 99%
“…26 This information should be discussed in order to empower parents/ caregivers in terms of providing preventative care for their children. 27 Collective measures are also important, such as a sugar tax and the proper labeling of unhealthy foods, which imply a reduction in the availability of foods with a high potential to develop chronic diseases, such as obesity, diabetes, and dental caries. 4 The model created in the present study showed that dental caries and socioeconomic status had a direct negative impact on the OHRQoL of schoolchildren.…”
Section: Discussionmentioning
confidence: 99%
“…Esses estudos mostraram que, em sua maioria, os meninos acima do peso, porém são as meninas que estão insatisfeitas com sua IC. (BRAZ et al, 2019;SILVEIRA;NEVES, 2019;MARTINI et al, 2020;PINHO et al, 2019). Meninas acima do peso e com insatisfação na IC foram identificadas em programas de incentivo à prática de atividades físicas (SILVA et al, 2020;SCHERR et al, 2019).…”
Section: Fonte -Autoria Própriaunclassified